Hand Gesture based Concept of Human - Mobile Robot Interaction with Leap Motion Sensor. Issue 25 (2019) - Ahmed, S.; Popov, V.; Topalov, A.; Shakev, N.
Abstract: A precise gestural control interface of a four-wheel mobile robot is presented. The introduced hand gesture based concept of human - mobile robot interaction is inspired by the approaches of Cyber-physical systems, which combine cyber and physical world solutions. The goal is to create an effective human-machine interface that will allow more intuitive interaction between the operator and the robot. Thus, a human operator can initiate and control various maneuvers via specific hand gestures. A KUKA youBot omnidirectional mobile platform and a Leap Motion Sensor have been used to implement and evaluate the proposed gestural control strategy.